Functional Analysis of the Pepper Ethylene-Responsive Transcription Factor, CaAIEF1, in Enhanced ABA Sensitivity and Drought Tolerance - Hong, Eunji; Lim, Chae Woo; Han, Sang-Wook; Lee, Sung Chul (Frontiers in Plant Science, 2017)
Abscisic acid (ABA) is a plant hormone that plays a critical role in the response to environmental stress conditions, especially regulation of the stomatal aperture under water-deficit conditions. The signal transduction occurring during the stress response is initiated by transcription of defense-related genes. Here, we isolated the pepper ethylene-responsive transcription factor CaAIEF1 (Capsicum annuum ABA Induced ERF 1). The CaAIEF1 gene was significantly induced after exposure to ABA, drought, and high salinity. Fusion of the acidic domain in the C-terminal region of CaAIEF1 to the GAL4 DNA-binding domain had a transactivation effect on the reporter gene in yeast. Further, the CaAIEF1-GFP fusion constructs localized in the nucleus. We used CaAIEF1-silenced plants and CaAIEF1-overexpressing (OX) plants to elucidate the biological function of CaAIEF1 in response to ABA and drought stress. CaAIEF1-silenced pepper plants and CaAIEF1-OX Arabidopsis plants displayed drought-sensitive and -tolerant phenotypes, respectively, which were characterized by regulation of transpirational water loss and stomatal aperture. In drought stress condition, quantitative RT-PCR analyses revealed that the expression levels of pepper stress-related genes were higher in CaAIEF1-silenced pepper plants than control plants. Moreover, expression levels of Arabidopsis stress-related genes were significantly reduced in CaAIEF1-OX plants compared with control plants in drought stress condition. Our findings suggest that CaAIEF1 positively regulates the drought stress response and the ABA signaling.